Effectiveness of Ivermectin among COVID-19 patients: A Randomized Controlled Trial - Muhammad Umar, Rizwana Shahid, Muhammad Mujeeb Khan, Uzma Hayat, Ayesha Nadar, Sheema Afzal, Muhammad Umar, Rizwana Shahid, Muhammad Mujeeb Khan, Uzma Hayat, Ayesha Nadar, Sheema Afzal; Muhammad Umar, Rizwana Shahid, Muhammad Mujeeb Khan, Uzma Hayat, Ayesha Nadar, Sheema Afzal, Muhammad Umar, Rizwana Shahid, Muhammad Mujeeb Khan, Uzma Hayat, Ayesha Nadar, Sheema Afzal (Journal of Rawalpindi Medical College, 2022)
Objectives: To determine the effectiveness of Ivermectin among COVID-19 patients in terms of mortality and biochemical / hematological attributes. Materials and Methods: A Randomized Controlled Trial (RCT) was carried out in Department of Infectious Diseases (DID) of Holy Family Hospital Rawalpindi during March 2021 through concurrent parallel study design. Apart from seeking Ethical approval for this research, DID was also licensed from Drug Regulatory Authority of Pakistan (DRAP) for this trial. Total 90 PCR positive COVID-19 patients were enrolled in this study via 1:1 randomization in experimental and control group without blinding. The control group received Standard of Care (SOC) starting from day 1 while experimental group was given SOC along with Ivermectin (200µg/kg) for 5 days. Study participants were assessed on day 0, 4, 7 and 10 for general symptoms through physical examination, blood oxygen saturation and diverse hematological and biochemical indicators in addition to adverse events. Data analysis was done by means of SPSS version 25.0. and Microsoft Excel 2010. Mean ± SD for age, length of hospital stay and time to PCR negativity were calculated. Independent sample t-test was applied to determine the mean difference in age, duration of hospital stay, time to PCR negativity, SpO2, oxygen supply, serum Hemoglobin, TLC, platelet count, Clinical Severity Score (CSS), urea and creatinine levels of both groups. The difference in secondary outcome (expiry / discharge) of both groups was compared by means of chi-square test. P-value ≤ 0.05 was considered significant. 95% Confidence Interval was also computed. Relative Risk (RR) was also measured to verify the effectiveness of Ivermectin in COVID patients Results: Males constituted the majority (56.7%) of our study participants. Statistically insignificant difference in mean age (P = 0.42) and mean length of hospital stay (P= 0.32) between experimental and control group subjects was observed. Mean time to PCR negativity was reported to be significantly less (P= 0.002) in experimental group. Significant improvement was seen in PCR negativity (P<0.05), mean Clinical Severity Score (CSS) (P0.02), mean hemoglobin level (P=0.03) and mean platelet count (P=0.03). Difference in health outcome of both groups was determined to be statistically insignificant (P<0.2, 95% CI (-0.20 – 0.12)). Relative Risk of 0.8 proved the protective effect of Ivermectin in COVID. Conclusion: Ivermectin was quite effective in reducing mortality and improving the health outcome in COVID-19 patients.